PENGARUH BRAND IMAGE, PROMOSI, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN AIR MINUM DALAM KEMASAN MEREK LE MINERALE : (Studi Kasus Pada Mahasiswa Prodi Manajemen Universitas Bhayangkara Jakarta Raya Angkatan 2021) - Putri, Elisa Nabila; Kurniawan, Dody; Husadha, Cahyadi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the independent variables consisting of Brand Image, Promotion, and Product Quality on the dependent variable, namely Purchasing Decisions, both simultaneously and partially. The approach used in this study is a quantitative method with a sampling technique using purposive sampling based on the Slovin formula. The population in this study were 127 Management Study Program Students at the University of Bhayangkara Jakarta Raya Class of 2021. With a sample size of 100 respondents. Based on the results of the partial test analysis (t-test), it was found that the Brand Image variable has a significant positive effect on Purchasing Decisions with a t-count of 4,950> 1,984 (t-table) and a significant value of 0.000 <0.05. Furthermore, the Promotion variable also shows a significant positive effect on Purchasing Decisions with a t-count of 12,465> 1,984 (t-table) and a significant value of 0.000 <0.05. Meanwhile, the Product Quality variable shows a positive but insignificant partial effect on Purchasing Decisions because the t-count is 1.737 < 1.984 (t-table) with a significant value of 0.86 > 0.05. In the simultaneous test (F test), it is known that the three independent variables together have a positive and significant effect on Purchasing Decisions with an F-count value of 113.152 > 2.70 (F table) and a significant value of 0.000 < 0.05. Meanwhile, the results of the determination coefficient test (R²) show that the relationship between Brand Image (X1), Promotion (X2), and Product Quality (X3) with Purchasing Decisions (Y) has a correlation level of 77.3%.